Persistent dysesthesias in involuted infantile hemangiomas: An uncommon complication in a common condition. Issue 5 (2nd August 2021) - Braun, Mitchell; Metry, Denise; Frieden, Ilona J.; Antaya, Richard J.; Mancini, Anthony J.; Kohn, Lucinda L.
Abstract: Background/Objectives: Infantile hemangiomas (IHs) are common benign vascular tumors of infancy. IHs tend to grow in the first few months of life and then gradually involute over years, often leaving fibrofatty residua or textural changes in their place. Classically, these lesions are painless throughout their entire natural history; however, we now report on seven patients with involuted IH with intermittent but persistent sensory symptoms. Methods: This is a multicenter case series in which members of the Birthmarks Focused Study Group of the Pediatric Dermatology Research Alliance (PeDRA) and the Hemangioma Investigator Group contributed patients with IH and dysesthesias from their clinical practices. Charts were then reviewed to document clinical details. Results: Seven patients were included, presenting at an average age of 14.6 years (range 3‐48 years) for complaints related to discomfort in the region of involuted IH. The majority (6/7) reported pain or tenderness to the area. One patient reported pruritus. All patients reported intermittent symptoms. The length of symptoms ranged between 4 months and 5 years. Treatment was attempted in 5/7 patients. Ice, oral propranolol, topical capsaicin, and intralesional triamcinolone partially improved symptoms. Conclusions: Persistent cutaneous dysesthesias were present in seven patients, in most cases many years after completion of involution. Further research is needed to fully elucidate the pathophysiology and optimal treatments for this IH complication.